0
$\begingroup$

$\int_0^n s (\int_0^s f(t) \, dt) \, ds = \int_0^n f(s) (\int_s^n t \, dt) \, ds $

The $s$ and $t$ in $f$ are just dummy variables of the same function.

Is there a way to start from the left hand side of this equation and show it is equal to the right hand side or vice-versa? The author of the paper that uses this relation only mentions the use of Fubini's Theorem to show it.

There is a geometric interpretation of this problem here with $f = 1$: Rearranging double integral and bounds

Edit: I see the process of it shown here without $s$ in the outer integral: Double integral and variable change problem

$\endgroup$
0
$\begingroup$

For convenience write $g(s,t):=s f(t)$. We are integrating $g(s,t)$ over the triangular region in $(s,t)$ space with vertices at $(0,0)$, $(n,0)$ and $(n,n)$. This is done by iterating the integrals: As $s$ is held fixed, you integrate $g(s,t)$ over $t$ from $t=0$ to $t=s$; then integrate the result over $s$ from $s=0$ to $s=n$. So to flip the order of integration you would hold $t$ fixed and integrate $g(s,t)$ over $s$ from $s=t$ to $s=n$; then integrate the result over $t$ from $t=0$ to $t=n$. In symbols: $$ \int_{s=0}^n\int_{t=0}^s g(s,t)\,dt\,ds=\int_{t=0}^n\int_{s=t}^n g(s,t)\,ds\,dt\tag{*} $$ Now you can argue step by step: $$ \begin{align} \int_{s=0}^n \left(s \int_{t=0}^s f(t)\,dt\right)ds &=\int_{s=0}^n\int_{t=0}^s sf(t)\,dt\,ds\\ &=\int_{s=0}^n\int_{t=0}^s g(s,t)\,dt\,ds\\ &\stackrel{(*)}=\int_{t=0}^n\int_{s=t}^n g(s,t)\,ds\,dt\\ &=\int_{t=0}^n\int_{s=t}^n sf(t)\,ds\,dt\\ &=\int_{t=0}^nf(t)\left(\int_{s=t}^n s\,ds\right)dt\\ &=\int_{s=0}^nf(s)\left(\int_{t=s}^n t\,dt\right)ds \end{align} $$ In the final step we swap dummy variables $s$ and $t$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.